Acknowledging a 'Missing History?'. Issue 2 (1st October 2014) - Doyle, Susan
A unique grassroots project is under way to write the first-ever textbook on the History of Illustration. The effort, which benefits from a base of over 30 writers internationally, is backed by a consortium of more than 60 educators, researchers, curators and illustration practitioners collaborating under the aegis of the History of Illustration Project (HIP). The volume, now in development with Fairchild Books (a Bloomsbury imprint), evolved initially through an online conversation about the need for more critical assessment of illustration and its history. Many of the points of that debate are detailed in the article that follows. The summary rationale for the HIP textbook (of which I am lead editor) is to expand the art historical investigation of illustration and address its synergistic relationship to history, science, visual culture and literature.